Inclusive Digital Transformation: A Techno Socialism Based IT Governance Model for Bandung City - Muhammad Rozahi Istambul; Parlindungan Parlindungan; Iwan Rijayana (Equivalent: Jurnal Ilmiah Sosial Teknik, 2026)
Background: Indonesia is facing rapid digital urbanization that exacerbate the unequal access to technology among urban sub-districts, which ultimately preventing peripheral and low-income people from accessing Smart City concept implementation. Furthermore, the success of Smart Cities in the country is also called into question, as illustrated by Bandung City as one of Indonesia's pioneers; where sub-districts at the core are clearly superior to those on the periphery in terms of internet penetration and digital literacy. Objective: This study describes the design of an IT governance framework that embraces technosocialism as a new ideal for tackling digital inequality in Bandung City. Methods: This study employs the Design Science Research (DSR) methodology to identify technology access issues in sub-districts and creating practical solutions to enhance community participation in Smart City initiatives, particularly those that are not balanced by increasing local access, as in Gedebage and Cibiru sub-districts. Results: Technosocialism served to target digital infrastructure improvements (high-speed internet access, cyberinfrastructure), develop customized trainings for digital literacy, and enable cross-sector collaboration. Nonetheless, these interventions reduced the challenges to digital inequities and made technology accessible for many of us. The original contribution to IT governance literature is that effects are not only dependent but also directly addressed by a combination of social equity and technological efficiency. The results contribute theoretical implications and practical recommendations for city governments to craft more inclusive policies that can be applied across cities worldwide. Conclusion: This research proved, through the DSR methodology that made a technosocialism-based IT governance framework effectively narrow the digital divide in Bandung City. Through targeted interventions, we've been able to increase access to technology and community participation by 40% in the most disadvantaged sub-districts; potential for a replicable model of inclusive Smart City governance in Indonesia -- and beyond.